The search for universal transdiagnostic and trans-therapy change processes: evidence for intolerance of uncertainty - McEvoy, Peter; Erceg-Hurn, D. (Pergamon, 2016)
The search for universal processes associated with symptom change across emotional disorders and different forms of psychotherapy offers hope of increased theoretical parsimony and treatment efficiencies. This study investigated whether intolerance of uncertainty (IU) is a universal process by examining whether changes in IU were associated with changes in symptoms across three different cognitive behavior therapy protocols for depression (n = 106), social anxiety disorder (n = 88), or generalized anxiety disorder (n = 62) in a community mental health clinic. IU was associated with reductions in repetitive negative thinking in all treatments, which is consistent with IU being a transdiagnostic and 'trans-therapy' process of change. Changes in IU were also associated with symptom relief in the social anxiety disorder and generalized anxiety disorder groups, but not in the depression group. Implications of these findings are discussed within the broader literature of transdiagnostic approaches to emotional disorders.